UMA PROPOSTA DIDÁTICA: A RESOLUÇÃO DE PROBLEMAS ATRAVÉS DO MÉTODO DE PÓLYA AMPARADO POR SISTEMAS DE ENSINO - Moura, Fabrício Marom de (2015)
The main focus of this work is to present the solution of problems supported by softwares as a pedagogical alternative in order to improve the teaching and the learning of mathematics content. In order to do this, the present work connects the aim of the National Curricular Parameters (PCN's), the technique described by Pólya in his book "How to solve it", along the possibility of utilization of programs such as: GeoGebra, Graphmatica, Spreadsheets and Maxima. It is known that many mathematics educators have shown interest for this subject of research. However, despite of all enthusiasm, few of them can put it into practice in the teaching-learning process. The solution of problems still exists as a complementary activity and is sometimes confused with solving exercises where the answer is not analyzed and the values found have no meaning for the student. The progressive scientific and technological evolution requires of teachers new ways to teach their students. In particular, the present work makes interesting connections between Mathematics and Informatics,extracting this union tools that stimulate curiosity, improve mathematical reasoning, making easy contents and concepts, and mainly allow the discovery of the path of resolution. In this way, we intend to show the true face of this teaching technique, by using Informatics, basing it and giving examples of how to implement activities that enable the student to develop mathematical concepts and processes, ability to solve problems, to reason, to communicate mathematically and as citizens. This research is based on bibliographical works that addresses issues related to teaching and learning of mathematical process.Some examples demonstrate that the mediation of computers brings new possibilities in solving problems. Concerning the last claim, it is expected that mathematics contribute to the formation of a citizen in its fullness, providing their integration as citizens in the workplace.